TINJAUAN FIKIH MUNAKAHAT TERHADAP BERITA PERNIKAHAN DUA WANITA KEMBAR DENGAN SEORANG LAKI-LAKI DI TRIBUNJABAR.ID - hamsah hudafi; Heri Firmansyah; Rizki Syahputra Nasution; Syahril Efendi (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
Marriage is an attachment relationship between a man and the woman he marries based on sacred and noble Islamic values. Marriage must obey and pay attention to the laws and regulations contained in fiqh munkahat to prevent wrong and invalid marriages. The wedding incident reported by Tribunjabar.id on July 18 2022 is one of the problems of marriage that violates rules and laws. And it is not valid from the perspective of munakahat fiqh studies. This article aims to explain marriage in an Islamic perspective and discuss the law of marriage between a man and two twin girls as quoted by Tribunjabar.id using the perspective of munakahat fiqh studies. The method in writing this article uses descriptive qualitative research. The results of the analysis concluded that every marriage procession must be in accordance with established Islamic law and it is a bad behavior for a man to marry two women who are siblings at the same time based on strong arguments.